Advances in molecular pathology of Ewing sarcoma - LIU Hengan, WANG Chaofu (Zhenduanxue lilun yu shijian, 2023)
Ewing sarcoma is a rare malignant small round cell mesenchymal neoplasm with a characteristic FET family-ETS family fusion gene, and is classified as undifferentiated small round cell sarcoma in the fifth revision of the WHO Classification of Tumors of Soft Tissue and Bone (2020）. Microscopically, Ewing sarcoma is composed of a monomorphic round cell population, accompanied by different degrees of neuroectodermal differentiation. Although surgery combined with chemotherapy has increased the 5-year survival rate of Ewing sarcoma to about 70%, the 5-year survival rate of patients with metastases at diagnosis is still less than 30%. With the rapid development of molecular pathology, the molecular mechanism of Ewing sarcoma has also become a focus of research. This article reviews the latest research progress on the unique pathological features, molecular mechanisms and genetic diagnostic criteria of Ewing sarcoma, in order to provide a new direction for the clinical diagnosis, treatment and prognosis of Ewing sarcoma.